Factors in studying employment for persons with disability : how the picture can change - Altman, Barbara (Emerald Publishing, 2017)
This collection examines less frequently anaylzed aspects of employment for persons with disabilities, offering a variety of approaches to the conceptualization of work, and how it differs across cultures, organizations, and types of disability.
Keywords: People with disabilities -- Employment -- Research.; elektronické knihy; electronic books